ANALISIS ENJOYMENT,EASE OF ACCESS, USEFULNESS,SOCIAL INFLUENCE,DAN MOBILE SHOPPING INTENTION PRODUK BLACK BERRYDI KOTA JEMBER - Febri Yudistian Putra; Sudaryanto Sudaryanto (STIE Mandala Jember, 2015)
The purpose of this study to the influence of enjoyment, ease of access, usefulness and social influence on attitude toward mobile shopping using mobile technology BB. This study categorized as explanatory research. The population in this study is the brand BlackBerry smartphone users who are members of the urban community members mailing list, which includes District Jember Sumbersari, Patrang, and Kaliwates. This research used purposive sampling method. The sample in this study was set at 115 people. Methods of data analysis using test instruments, test the normality of data, and pathway analysis. The results of this study indicate that the variable enjoyment significantly influence the attitude on mobile shopping. Ease of access variables have a significant effect on mobile shopping attitude. Usefulness significant effect on mobile shopping attitude. Influence of social variables have a significant effect on mobile shopping attitude. Variables significant effect mobile shopping enjoyment intention. Variables significantly affect ease of access mobile shopping intention. Variables significant effect usefulness of mobile shopping intention. Variables significant effect of social influence mobile shopping intention .